ANALISA PROKSIMAT COOKIES DENGAN SUBSTITUSI TEPUNG LOKAL - Wahyu Kanti Dwi; Anita Wulandari (Agroindustrial Technology, University of Trunojoyo Madura, 2022)
Snacking the activities food into the habit of someone. One of the snacks that are commonly consumed is cookies. Cookies are made from wheat flour as the main ingredient. Wheat imports in 2020 are as many as a million tons and are still high. So it is necessary to substitute wheat flour with local flour to reduce wheat flour consumption. Utilization of non when local wheat flour is innovation latest trend, especially for the bakery industry because wheat flour price fluctuates so bakery producers change non-wheat flour with flour. The purpose of this research is to determine the proximate analysis of cookies from the source of local flour, namely, rice flour corn, soybeans, sweet, and basil. The utilization of local flour may be a functional food source and reduce dependence on wheat flour. The research design used a Completely Randomized Design. After that, proximate analysis of cookies. The results showed that the proximate analysis of cookies following SNI was the analysis of protein, carbohydrates, water, ash, and crude fiber. Cookies with good proximate analysis results are cookies from purple sweet potato and corn flour. Comparison of purple yam flour and flour (75%: 25%) and corn flour and wheat flour (75%: 25%). The use of local flour can reduce wheat flour on cookies.